2016
DOI: 10.1038/celldisc.2016.28
|View full text |Cite
|
Sign up to set email alerts
|

JUN dependency in distinct early and late BRAF inhibition adaptation states of melanoma

Abstract: A prominent mechanism of acquired resistance to BRAF inhibitors in BRAFV600-mutant melanoma is associated with the upregulation of receptor tyrosine kinases. Evidences suggested that this resistance mechanism is part of a more complex cellular adaptation process. Using an integrative strategy, we found this mechanism to invoke extensive transcriptomic, (phospho-) proteomic and phenotypic alterations that accompany a cellular transition to a de-differentiated, mesenchymal and invasive state. Even short-term BRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 92 publications
6
71
0
Order By: Relevance
“…The drug‐tolerant state is driven by increased expression of MITF and c‐JUN and is characterized by a mesenchymal phenotype . Our data demonstrate that the combination of PLX4720 and palbociclib induces either cell death or senescence in the majority of cells, clearly indicating that the combination overcomes the PLX4720 induced mesenchymal phenotype.…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…The drug‐tolerant state is driven by increased expression of MITF and c‐JUN and is characterized by a mesenchymal phenotype . Our data demonstrate that the combination of PLX4720 and palbociclib induces either cell death or senescence in the majority of cells, clearly indicating that the combination overcomes the PLX4720 induced mesenchymal phenotype.…”
Section: Resultsmentioning
confidence: 73%
“…Resistance to BRAF inhibitors is associated with an initial reversible nonmutational drug‐tolerant state that leads to the emergence of mutated permanently resistant clones . We have previously demonstrated that treatment of melanoma cell lines for 3 weeks with PLX4720 leads to this drug‐tolerant state .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, these observations support that dedifferentiation and MAPK-reactivation routes of BRAF resistance are not mutually exclusive. In some cases, dedifferentiation can be a transient response of adaptive resistance (Fallahi - Sichani et al, 2017; Sun et al, 2014; Titz et al, 2016), and provide a reservoir of cells allowing for expansion or evolution of resistant clones with genetic mechanisms that enable return to the parental differentiation state (Ramirez et al, 2016). In alternate cases, the dedifferentiation state can be stabilized, such as through loss of SOX10 by epigenetic reprogramming (Shaffer et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Such networks of signaling pathways are complex and stochastic in nature, and recent efforts in identifying key players are starting to emerge in the literature. JUN and a protein kinase C (PKC) isoform were recently identified as main drivers of BRAFi resistance (Titz et al, ), whereas p‐21‐activated kinase (PAK) was found to be pivotal in resistance to combinatory MEKi and BRAFi therapy (Zhang et al, ). These studies reveal important insights into the biology of melanoma, and cell‐intrinsic mechanisms of therapy resistance.…”
Section: Introductionmentioning
confidence: 99%